Sometimes they Come Back: Recidivism and the Adult Imprisonment of Formerly Incarcerated Serious And Violent Juvenile Offenders - Trulson, Chad R. (American journal of criminal justice, 2024)
This study examines the adult imprisonment outcomes of a cohort of serious and violent juvenile offenders released from Texas state juvenile correctional facilities during their transition from adolescence to early adulthood. We distinguish incarceration in the adult prison system as resulting from a new offense or as the result of a revocation for a technical supervision violation. Of the sample (n = 709), 37% were incarcerated in Texas’ adult prison system within two years following their release from state juvenile incarceration—16% were incarcerated for a new offense and 21% were incarcerated for revocation as a result of a technical violation of supervision. Results indicate that race, being a sexual offender, gang affiliate, engaging in violent institutional misconduct as a juvenile ward, being under supervised release, and age at initial juvenile incarceration were determinants of adult incarceration for any reason. Similar determinants of incarceration were found examining incarceration for offenders released under community supervision. Prior placements as a juvenile and gang affiliation were correlated with incarceration for a new offense. Research and policy implications are discussed.